The Collaborative Nature of Innovation - Keith Sawyer (Washington University Journal of Law & Policy, 2009)
This Article argues that current intellectual property law is based on an inaccurate representation of how innovation actually occurs. It provides an alternate explanation of the innovative process and proposes and intellectual property protection policy better suited to that scheme.
Keywords: Technological innovations; Intellectual property; Operating systems (Software); Software licensing